Effect of Ce-doping on microstructure and electrical properties of LaAlO3 ceramics. Issue 4 (15th February 2023) - Xue, Yan; Deng, Wenye; Liu, Yuyu; Bai, Xuelian; Chen, Xianghui; Zhao, Pengjun; Pan, Ye; Zhang, Huimin; Chang, Aimin; Xie, Yongxin
Abstract: A series of novel negative temperature coefficient (NTC) thermistor materials based on La1- x Ce x AlO3 (0 ≤ x  ≤ 0.2) ceramics were synthesized via the solid-state route. X-ray diffraction results confirmed the successful doping of Ce in the La1- x Ce x AlO3 crystal and the formation of a good solid solution. Scanning electron microscopy results indicated that Ce doping is beneficial for grain growth and reduces the porosity of the samples. With the increase in the Ce doping amount, the average grain size increased from 2.1793 to 10.7344 μm, and densities of the ceramics increased from 93.15% to 99.26%. The temperature vs resistance curve indicated that Ce doping reduces the resistivity of LaAlO3 materials, while reducing the B200/1400 value of the LaAlO3 ceramic. For a doping amount of 0.2, the B200/1400 value of the LaAlO3 ceramic decreased from 18175.1 to 4897.7K, and the resistivity at 1000 °C decreased from 68971.87 to 1105.15 Ω cm. In addition, the La1- x Ce x AlO3 (0 ≤ x  ≤ 0.2) series materials exhibited good linear NTC characteristics. X-ray photoelectron spectroscopy results revealed that the resistivity of the LaAlO3 materials decreased after Ce doping owing to the transformation between the Ce 4+ and Ce 3+ valence states，and the concentration of Ce 3+ increased with the increase in the Ce doping amount. Ce 3+ increases the concentration of oxygen vacancies, decreasing the resistance. Impedance analysis findings suggested that the resistance of the La1- x Ce x AlO3 (0 ＜ x  ≤ 0.2) material mainly originates from the grain. These results indicate that Ce doping is an effective method to reduce the resistivity of LaAlO3 . Consequently, La1- x Ce x AlO3 (0 ≤ x  ≤ 0.2) is a promising material for NTC applications.